PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI LPP-RRI BUKITTINGGI - Defri Edasa; Elsanra Eka Putra (Jurnal Riset Manajemen Bisnis dan Publik, 2015)
This study aims to find: 1) the effect of leadership style on work motivation, 2) the effect of work environment on work motivation, 3) the effect of leadership style on the performance, 4) the effect of work environment on performance, 5) the effect of work motivation on the RRI Bukittinggi employee performance. Type of research is ex post-facto, the study population is employee of RRI Bukittinggi. Proportional sampling technique is Proportional cluster sampling. Samples totaling 76 people. Primary data was collected through a questionnaire using a Likert scale models that have been tested validity and reliability. The data analysis technique used is the Path Analysis (Path Analysis). The results of the study are: 1) There is a positive and significant impact of leadership style on work motivation, 2) There is a positive and significant impact of work environment on work motivation, 3) There is a positive and significant impact of leadership style on the performance, 4) There is a positive and significant impact of work environment on the performance, 5) There is a positive and significant impact of work motivation on the RRI Bukittinggi employee performance . In terms of direct and indirect influence of leadership style, work environment and work motivation to employe of LPP RRI Bukittinggi amounted to 38.8%, found that work motivation had the greatest influence of 14.82%. This suggests that an understanding of the work motivation has a major role to the RRI Bukittinggi employee performance Keywords : Leadership Style, Work Environment, Work Motivation, Performance